Does SIZE matter?: Liquidity provision by the Nasdaq anonymous trading Facility - Bruce Mizrach (Rutgers University, Department of Economics, 2005)
I examine the effects of Nasdaq's introduction of an anonymous trading facility called SIZE. I compare SIZE to competing ECNs in terms of liquidity and market impact. Despite rapid growth, SIZE has not yet attained a significant market share and rarely influences short-run price evolution. I conclude with discussion of the Nasdaq-ECN mergers and speculate about a role for SIZE in trading listed securities.
Keywords: G14; G20; 330; ECN; market impact; super montage; total view; Börsen-Informationssystem; Börsenumsatz; Wertpapierhandel; Wertpapierbörse; USA